Peran Guru Profesional sebagai Fasilitator Pembelajaran yang Inovatif dan Kreatif di Era Digital - Munawir Munawir; Maulidah Fahdia; Arum Lestari (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to examine the role of professional teachers as facilitators in fostering creative and innovative learning in the digital era. The background of this research lies in the challenges posed by globalization and technological advancements, which demand transformation in the educational system. In this context, teachers are positioned not merely as knowledge transmitters but as active companions in the learning process. The approach used is descriptive qualitative through literature review. The findings indicate that professional teachers play a vital role in integrating technology to create interactive, collaborative, and meaningful learning experiences. Additionally, the article highlights the importance of enhancing teachers’ digital competencies as part of the professionalism required to meet the demands of 21st-century education.